Exploring the Effects of Teacher’s Nonverbal Communication on EFL Students' Academic Motivation - Mutia Asisyifa; Maemuna Muhayyang; Nur Aeni (Universitas Islam Negeri Palopo, 2025)
Teacher’s nonverbal communication significantly effects students’ learning experiences, particularly in EFL Islamic classroom context where language and motivation are closely linked. This study examined the effects of teachers’ nonverbal communication on students’ academic motivation using an explanatory sequential mixed-methods design. Quantitative data were collected from 60 students through questionnaires measuring seven aspects of nonverbal communication namely proxemics, haptics, kinesics, chronemics, oculesics, physical environment, and paralanguage and three aspects of motivation that is, autonomy, competence, and relatedness. Qualitative data were obtained through classroom observations and interviews with ten selected students. Findings revealed that kinesics and proxemics received the highest ratings, indicating active use of gestures and classroom movement to engage students. Haptics and paralanguage scored lowest, suggesting limited use due to cultural norms. Correlation and regression analyses indicated a strong positive relationship between teachers’ nonverbal communication and student motivation. Observations confirmed that smiling, nodding, using hand gestures, and approaching students created a positive and low-anxiety learning atmosphere. Interviews supported these results, with students expressing greater confidence, comfort, and willingness to participate when teachers-maintained eye contact, used expressive gestures, and adjusted their proximity. This study highlights the importance of nonverbal behaviors in fostering a motivating EFL learning environment. Teachers’ awareness and intentional use of such cues can strengthen engagement and emotional connection, even in culturally specific settings.